The Effect of Continuous Ventilation on Thiol-Disulphide Homeostasis and Albumin-Adjusted Ischemia-Modified Albumin During Cardiopulmonary Bypass - Ozgunay,Seyda Efsun (2019)
Abstract Objective: To investigate the effect of continuous lung ventilation with low tidal volume on oxidation parameters, such as thiol/disulphide homeostasis and albumin-adjusted ischemia-modified albumin (AAIMA), during cardiopulmonary bypass (CBP) in coronary artery bypass grafting (CABG). Methods: Seventy-four patients who underwent elective CABG with CPB were included in the study. Blood samples were taken in the preoperative period, 10 minutes after CPB, and six and 24 hours postoperatively. Patients were assigned to the continuous ventilation group (Group 1, n=37) and the non-ventilated group (Group 2, n=37). The clinical characteristics, thiol/disulphide homeostasis, ischemia-modified albumin (IMA), and AAIMA levels of the patients were compared. Results: A significant difference was found between the groups regarding native thiol, total thiol, and IMA levels at the postoperative 24th hour (P=0.030, P=0.031, and P=0.004, respectively). There was no difference between the groups in terms of AAIMA. AAIMA levels returned to preoperative levels in Groups 1 and 2, at the 6th and 24th postoperative hours, respectively. Length of hospital stay was significantly shorter in Group 1 (P<0.001) than in Group 2. Conclusion: Continuous ventilation during CPB caused an increase in native and total thiol levels, an earlier return of AAIMA levels, and shorter hospital stay. Continuous ventilation may reduce the negative effects of CPB on myocardium (Table 2, Figure 1, and Reference 31).